The Design and Development of an Innovative and Environment Friendly Pilot Unit for the Transformation of Used Cooking Oils into Biodiesel in the City of Ifrane, Morocco - El Hamzaoui, Ismail; El Asli, Abdelghani; Mitouilli, Ezzaki; El Kihal, Mohammed; Adwan, Maryam; Achghani, Ismail; Jadid, Mohamed (International Renewable and Sustainable Energy Conference (Print), 2021)
The improper disposal of used cooking oils (UCO) in the environment represents significant health and environmental hazard. This paper presents a viable solution to the improper management of UCOs in the city of Ifrane, Morocco (14000 inhabitants). The solution consists of the collection of the city's UCOs and their transformation into useful biodiesel. The project has been developed over the past four years and included multiple levels of intervention: research, engineering, social engagement, logistics and economics. In this paper, we focus solely on the technical and engineering design aspects of the project. An average of 300 liters of UCOs was collected each week from the various collection points in the city. A pilot unit with a production capacity of 250 liters of biodiesel per batch was developed: schematics, automation, and process flow are discussed. The pilot unit presented several opportunities for innovation beyond what is found in most literature on the subject. Solar energy and biomass are used to fulfill the heat requirement of the chemical reactions. The recycling of methanol and glycerol are performed. The entire transformation process is automated using open-source Arduino microcontrollers and switch relays. The biodiesel yield is estimated to be between 85% and 93% of the transformed UCO in about two hours of reaction. This work can be used by individuals, NGOs, actors in academic institutions, and local authorities as inspiration when tackling the issue of improper disposal of UCOs in their area from a technical design point of view.